Current Account Developments in New Member States of the European Union : Equilibrium, Excess, and EU-Phoria - Rahman, Jesmin (IMF Working Papers; Working Paper, 2008)
This paper analyzes current account (CA) developments in the following 10 new EU members states: Czech Republic, Bulgaria, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia and Slovenia. During the last 15 years, these countries, on average, have run CA deficits that are considerably higher than the average CA deficit of other developing countries. However, more recently, a diverging pattern has emerged among these countries with one group, consisting of the Baltic countries, Bulgaria and Romania, experiencing rapid widening, while the others seeing a stabilization in their CA balances. Using panel data for 59 countries, this paper empirically investigates the following three questions: Are higher average deficits in EU-10 explained by medium-term macroeconomic fundamentals? What explains the diverging CA behavior among EU-10? And finally, how challenging is it for the group experiencing rapidly widening CA deficits to reverse the trend?.